Pemanfaatan Metode User Centered Design Pada Aplikasi E-Rapor Berbasis Website Di SDN 11 Rantau Bayur - Mahyudin Mahyudin; M.Rudi Sanjaya (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2023)
SD Negeri 11 Rantau Bayur is a public educational institution located in Banyuasin Regency. The school has been accredited with grade B and implements the 2013 curriculum in teaching and learning activities. However, SD Negeri 11 Rantau Bayur still uses manual methods in evaluating and recording student grades, such as making report cards, grade legers, and recapitulating student grades. This is an obstacle for teachers in measuring the development of students' abilities optimally because the results of the recap of student grades can only be seen at the end of the semester. Therefore, SD Negeri 11 Rantau Bayur needs a website-based report card application with an effective and efficient interface design. The design of the interface aims to provide an overview in the application of the report card application that can improve the efficiency of managing and recording student grades. This interface design is done using the User Centered Design (UCD) method, which allows users to participate in the application design process. This allows users to provide input and suggestions regarding the interface and desired features. After the design was completed, the prototype design of the report card application was evaluated using the Heuristic Evaluation & Webuse (Website Usability Evaluation) questionnaire.